HUBUNGAN LEMBAR KERJA PESERTA DIDIK BERBASIS CAT TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Silaban, Patri Janson; Hasibuan, Asnita (Unversitas Katolik Santo Thomas, 2021)
To find out the development, effectiveness, relationship, response, enhancing the ability of mathematical understanding with the development of learner-based worksheets CAT six graders Methodist-12 field in the material integer arithmetic operations. This research is included in research and development (Research and Development). As that R&D is a research method used to produce certain products and test the effectiveness of these products. This method is used with the aim of developing CAT-based student worksheets for grade VI SD Methodist-12 Medan on integer arithmetic operations. The study found, namely (1) CAT-based Student Worksheets are feasible to be developed and good to be applied in learning, (2) CAT-based Student Worksheets have a positive and significant relationship with students' mathematical understanding abilities, (3) CAT-based Student Worksheets have a positive effect on students' mathematical understanding abilities. Teachers can create and present the teaching materials with exciting creativity, media with an attractive creativity, practice questions that are presented in accordance with the material, enhancing the creativity of teachers in designing learning media.